The use of deliberate practice in simulation-based surgical training for laparoscopic surgery – a systematic review - Dakshitha Wickramasinghe; Jonathan Vincent (BMC Medical Education)
Abstract Background Minimally Invasive Surgery (MIS) has necessitated specialized training beyond traditional open surgical methods. Simulation-Based Surgical Training (SBST) offers a promising alternative, but its instructional design varies significantly. Deliberate Practice (DP), a concept originating from expertise research, may enhance SBST effectiveness. This systematic review evaluates the integration of DP within SBST for MIS. Methods A systematic literature search was conducted using MEDLINE, EMBASE, SCOPUS, ERIC, and Google Scholar, covering publications up to January 31, 2024. Randomized controlled trials and observational studies implementing DP in SBST for laparoscopic surgery were included. Data extraction focused on DP elements (task design, feedback, and repetition), learner motivation, training structure, and outcome measures. Study quality and risk of bias were assessed using the RoB2 and ROBINS-E tools. Results Ten studies met inclusion criteria, comprising five randomized controlled trials and five observational studies. Study participants were predominantly surgical trainees, with training programs utilizing box trainers or virtual reality simulators. DP-informed SBST was consistently associated with improved psychomotor skills, particularly when feedback was immediate, and training incorporated structured task progression. Task design varied, with only two studies tailoring training based on pre-existing skill levels. Stepwise task progression was reported in five studies. Feedback was delivered through either human mentors or automated simulator feedback, with mixed findings on their comparative effectiveness. While automated feedback ensured immediacy, human supervision was often deemed superior in guiding skill acquisition. Repetition was widely integrated, though session duration and spacing varied across studies. Learner motivation was explicitly assessed in one study, while two others incorporated motivation-enhancing interventions such as gamification and mentoring. DP-informed SBST resulted in improved accuracy, speed, confidence, and objective skill ratings. Some control groups also demonstrated skill improvements, though typically reaching performance plateaus earlier and at lower competency levels. Variability in DP adherence across studies influenced outcomes, with the most structured programs yielding the greatest benefits. Conclusions DP-informed SBST is a promising approach for developing MIS skills. Adherence to DP principles significantly enhances skill acquisition but limited by resource requirements. Future research should focus on optimizing DP integration within SBST to maximize its impact on surgical education.